Periods of Limitation in Russian Federation and Foreign Countries - Vasiliy Aleksandrovich Tsvetkov (Сибирское юридическое обозрение, 2011)
The article deals with the essence and the procedure of a period of limitation. The author researches the difference between the legal regulation of a limitation period in Russia and foreign countries and introduces ways of the development of civil legislation.